A multivariate metabolic imaging marker for behavioral variant frontotemporal dementia. Issue 1 (29th August 2018) - Nazem, Amir; Tang, Chris C.; Spetsieris, Phoebe; Dresel, Christian; Gordon, Marc L.; Diehl‐Schmid, Janine; Grimmer, Timo; Yakushev, Igor; Mattis, Paul J.; Ma, Yilong; Dhawan, Vijay; Eidelberg, David; et al.
Abstract: Introduction: The heterogeneity of behavioral variant frontotemporal dementia (bvFTD) calls for multivariate imaging biomarkers. Methods: We studied a total of 148 dementia patients from the Feinstein Institute (Center‐A: 25 bvFTD and 10 Alzheimer's disease), Technical University of Munich (Center‐B: 44 bvFTD and 29 FTD language variants), and Alzheimer's Disease Neuroimaging Initiative (40 Alzheimer's disease subjects). To identify the covariance pattern of bvFTD (behavioral variant frontotemporal dementia–related pattern [bFDRP]), we applied principal component analysis to combined 18F‐fluorodeoxyglucose–positron emission tomography scans from bvFTD and healthy subjects. The phenotypic specificity and clinical correlates of bFDRP expression were assessed in independent testing sets. Results: The bFDRP was identified in Center‐A data (24.1% of subject × voxel variance; P  < .001), reproduced in Center‐B data ( P  < .001), and independently validated using combined testing data (receiver operating characteristics–area under the curve = 0.97; P  < .0001). The expression of bFDRP was specifically elevated in bvFTD patients ( P  < .001) and was significantly higher at more advanced disease stages ( P  = .035:duration; P  < .01:severity). Discussion: The bFDRP can be used as a quantitative imaging marker to gauge the underlying disease process and aid in the differential diagnosis of bvFTD.